IOT-ENABLED REAL-TIME PRODUCT LIFECYCLE MANAGEMENT: ADVANCING MEDICAL DEVICE MANAGEMENT IN HEALTHCARE - Jasleen Singh Saini (INTERNATIONAL JOURNAL OF RESEARCH IN COMPUTER APPLICATIONS AND INFORMATION TECHNOLOGY (IJRCAIT), 2025)
This article explores the transformative integration of Internet of Things (IoT) technologies with Product Lifecycle Management (PLM) systems in healthcare settings, focusing on medical device management and monitoring. The article examines how IoT-driven data integration enables real-time tracking, management, and optimization of medical devices throughout their lifecycle. The article investigates the implementation framework, including data collection architectures, security protocols, and integration with existing healthcare systems. Through comprehensive analysis of case studies involving wearable health monitors, connected diagnostic equipment, remote patient monitoring, and predictive maintenance systems, the article demonstrates the significant improvements in operational efficiency, cost optimization, and patient safety. The article also addresses the challenges healthcare organizations face during implementation, including technical infrastructure limitations and data management complexities. Furthermore, the article explores emerging technologies, industry trends, and future research opportunities in healthcare IoT-PLM integration. The article highlights how this technological convergence has revolutionized healthcare delivery, enhanced device management practices, and improved patient care outcomes while providing substantial financial benefits for healthcare organizations.